PERLINDUNGAN PEREMPUAN BAWAH UMUR DARI PERILAKU PEDOFILIA: SUATU PENERAPAN MODEL KOLABORASI PENTAHELIX - Puja Aulia Dinasty; Hary Priyanto; Niko Pahlevi Hentika (Nusantara Hasana Journal, 2025)
Children are the future of the nation. Sexual violence against children by pedophile perpetrators results in physical, mental, social, psychosocial and sexual suffering. The important task of the government is to protect children, take action against perpetrators, and reveal acts of pedophelia. Collaboration between various parties is needed so that the problem of pedophelia is handled well. This research is guided by qualitative descriptive principles. The aim of the research is to analyze and interpret the collaboration model in handling and overcoming pedophilia in Banyuwangi Regency. According to the findings research, the threat of pedophelia is a crucial social problem, so it requires serious attention from all components of society. The impact of pedophile behavior not only leads to physical and psychological aspects, but also damages social order and human values. The recommendation from this research is that all elements in the pentahelix continue to collaborate to complement each other. With continued commitment, it is hoped that a safe environment will be created for children and reduce the number of pedophelia cases in Banyuwangi Regency.